Diagnóstico, propuesta e implementación de un plan de gestión de residuos sólidos municipales en la zona urbana del distrito de quiruvilca - santiago de chuco. - Gamboa Vicente, Jhoel Alois (2015)
This work was carried out in order to submit a plan of management of municipal solid waste in urban area Quiruvilca district, to improve the traditional waste management and improve its reuse and disposal. Among the activities starting point was formed basically by identifying the current status of solid waste management in the study area, the first step diagnosis of the real situation, the conditions, characteristics and resources it determined held for the management of waste by the municipality. As history has to be the Quiruvilca district is located at the head of Moche River Basin, with an area of 549 km2, currently it has 27 hamlets scattered across the surface of the District, in the course of the study he had a range in the 10 districts of the urban population Quiruvilca District. The current urban population was also identified in the District for the current year, calculating an estimated 7067 habitants, also the socioeconomic and cultural characteristics of the population. In the study area, it was observed a traditional waste management because the arrangement is done in open dumps, recovery of reusable materials is done by people of very low income, amid conditions of safety and inadequate hygiene, also the practice of dumping waste into rivers or incinerate lack of sanitation service, make the District confronts a health and environmental pollution. The characterization study of municipal solid waste, where the per capita generation, characteristics and composition of municipal solid waste generated in the district was determined is then performed, yielding a per capita generation of 0.875 kg/day in the case of household waste, also the per capita generation according to line of business it was obtained for commercial establishments 2.94 kg/day, hotels and restaurants 9,078 kg/day, market stalls 1.730 kg/day, educational institutions 6,306 kg/day and the product of street sweeping 1,176 kg/day. In the most important characteristics density it was determined taking for domestic waste a value of 385.84 kg/m3, also the density in non-residential waste is determined according to each line of business, being for commercial waste 50.9 kg/m3, for markets 171.08 kg/m3, for educational institutions 68.24 kg/m3 and hotel-restaurants 438.98 kg/m3, making an average of 182.31 kg/m3. The physical composition of the solid waste generated in the District, resulting in a higher percentage the following, inert waste (coal ash) with a total of 77.09%, 8.29% organic waste, medical waste with 3.39%, metal waste 1.17%, 1.14% cardboard and plastic with 0.94%. The moisture content of solid waste was determined according to the per capita generation of the most representative neighborhoods, earning on average 46.55% moisture. According to the data obtained in the study of characterization, projections were determined to generation per capita and accumulated weight for the following two years. For proper management of solid waste is required to implement the plan of solid waste management that seeks to implement policies to improve the practice of segregation at source, reuse and disposal of municipal solid waste being vital the participation of authorities as well as the general population.